2022
DOI: 10.1021/acs.inorgchem.2c02730
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Isocyanide Complexes of Technetium under Steric and Electronic Control

Abstract: Reactions of the alkyl isocyanide fac-[Tc­(CO)3(CNR)2Cl] complexes (2) (CNR = CN n Bu or CN t Bu) with the sterically encumbered isocyanide CNp-FArDarF2 [DArF = 3,5-(CF3)2C6H3] allow a selective exchange of the carbonyl ligands of 2 and the isolation of the mixed-isocyanide complexes mer,trans-[Tc­(CNp-FArDarF2)3(CNR)2Cl] (3). Depending on the steric requirements of the residues R, the remaining chlorido ligand can be replaced by another isocyanide ligand. Cationic complexes such as mer-[Tc­(CNp-FArDarF2)3(CN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(52 citation statements)
references
References 93 publications
(165 reference statements)
4
44
0
1
Order By: Relevance
“…A more detailed assessment of the influence of electronic factors on the coordination behavior of highly substituted aryl isocyanides is available for a number of chromium(0) compounds, where a special role for aryl isocyanides with electron-withdrawing substituents was found [ 10 ]. Similar results were derived very recently for carbonyltechnetium(I) compounds, which react with differently substituted isocyanides in very different manners ( Scheme 1 ) [ 11 ]. It became evident that simple alkyl isocyanides were not able to replace carbonyl ligands, while this was readily possible with aryl isocyanides which have a fluorine substituent in 4-position.…”
Section: Introductionsupporting
confidence: 87%
See 4 more Smart Citations
“…A more detailed assessment of the influence of electronic factors on the coordination behavior of highly substituted aryl isocyanides is available for a number of chromium(0) compounds, where a special role for aryl isocyanides with electron-withdrawing substituents was found [ 10 ]. Similar results were derived very recently for carbonyltechnetium(I) compounds, which react with differently substituted isocyanides in very different manners ( Scheme 1 ) [ 11 ]. It became evident that simple alkyl isocyanides were not able to replace carbonyl ligands, while this was readily possible with aryl isocyanides which have a fluorine substituent in 4-position.…”
Section: Introductionsupporting
confidence: 87%
“…The results obtained during reactions of tricarbonyltechnetium(I) complexes and other metal centers with isocyanides strongly indicate that this class of ligands should not be regarded in the same undifferentiated way as carbonyl surrogates, although a few correlations between the properties of some isocyanides and their highest occupied molecular orbitals (HOMO) and lowest unoccupied molecular orbitals (LUMO) have been discussed in the past [ 23 , 24 , 25 , 26 ]. It has been found that electronic as well as steric effects strongly influence their coordination capabilities [ 10 , 11 , 12 , 13 , 14 , 15 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. The electronic effects can best be described by a consideration of the electrostatic potentials located at the donor carbon atoms.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations